Resources and livelihood in mountain Areas of South East Asia : (Margraf publishers, 2006)
This book deals with these issues and it will serve: students to better understand the socio-economic systems and development in rural areas, scientists to not only compare their own experiences but also to stimulate academic and scientific discussion for the bettermant of the research and staf f in practical work of implementation and policy decision-makers to consider the future long-term relevance of problem-solving strategies directly related to needs of the rural people ;